PENGEMBANGAN MEDIA APRON HITUNG PADA ANAK USIA DINI - Nurul Aulia; Dewi Fitria (Jurnal Educhild : Pendidikan dan Sosial, 2023)
This development research aims to determine the feasibility of learning media, namely counting apron media equipped with a guidebook for using media in early childhood learning activities. This research is a type of research and development (R&D) with the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The focus of this research is the development of arithmetic apron media equipped with a guidebook for media use to facilitate teachers in making and using arithmetic apron media. The instrument used to collect data is a questionnaire given to validators, namely material expert validators, and media expert validators. Interview instruments given to teachers before and after using the counting apron media developed in this study.  Based on the validation results from the material expert validator, the score was 94.5% with the category "Very Feasible", and the results of the media expert validator obtained a score of 98.4% with the category "Very Feasible". The results of the teacher interview also stated that the counting apron media is suitable for use in early childhood learning activities. Based on the assessment score criteria, it can be said that the Calculation Apron Media Development in Early Childhood equipped with a guidebook for using the developed media is valid and very feasible to use in the early childhood learning process.